Eco-theology: Reimagining the image of God in the context of creation and care in Africa - Hove, Rabson (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2024)
Africa and the rest of the world are at risk due to climate change and ecological crisis. The current severe cold fronts, flooding, and heatwaves sweeping across Africa, particularly Southern Africa, demonstrate that more is to come. The abnormal weather patterns know no seasons. The apparent results include starvation due to poor harvests and loss of homes, property, livestock, and lives due to disruptive rains and heat waves. The impact of climate change is visible in ecological damage. All this calls for a theological discourse that seeks to unpack some ways of caring for creation and the environment to mitigate against the challenges posed by climate change. The critical question is what theological tools the church could use to make meaningful contributions in responding to the challenges of climate change in Africa. Hence, the suggested theological engagements of the image of God about caring for creation. This paper seeks to explore the theology of the image of God, which provides theologians and the church with the basis to respect, protect, and care for the environment. It will discuss how understanding God's image helps the church implement practical ways of environmental care given the current dangers of climate change and ecological crisis in Africa. The paper contributes to the theological discourse of environmental care.